2022
DOI: 10.1021/acschembio.1c00652
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Gene Knockdown on CD22-Expressing Cells by Chemically Modified Glycan Ligand–siRNA Conjugates

Abstract: Extrahepatic targeted delivery of oligonucleotides, such as small interfering RNA (siRNA) and antisense oligonucleotides (ASOs), is an attractive technology for the development of nucleic acid-based medicines. To target CD22-expressing B cells, several drug platforms have shown promise, including antibodies, antibody–drug conjugates, and nanoparticles, but to date CD22-targeted delivery of oligonucleotide therapeutics has not been reported. Here we report the uptake and enhancement of siRNA gene expression kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The selectivity of the target mRNA was also confirmed using three types of target sequences. The gene silencing activity of the siB2M(h) conjugate was weaker than that of the siHPRT1-a conjugate in our previous report ( 57 ), and the same tendency was observed in this study. Although optimization of the sequence and modification pattern in this study has not been fully investigated, these results indicate that siRNA optimization is also important for validating the conjugate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The selectivity of the target mRNA was also confirmed using three types of target sequences. The gene silencing activity of the siB2M(h) conjugate was weaker than that of the siHPRT1-a conjugate in our previous report ( 57 ), and the same tendency was observed in this study. Although optimization of the sequence and modification pattern in this study has not been fully investigated, these results indicate that siRNA optimization is also important for validating the conjugate.…”
Section: Discussionsupporting
confidence: 91%
“…Our CMM–siRNAs exhibited enhanced uptake and gene silencing effects compared with siRNA and C3N-siRNA as non-CD206-binding compounds (Figures 4 and 5 ). In other studies, multivalent sugar ligand-conjugated siRNAs have been shown to enhance gene silencing, accompanied by increased valency-dependent uptake ( 56 , 57 ). As expected, valency-dependent uptake, gene silencing, and protein downregulation were observed compared with CMM1–siRNA and CMM4–siRNA.…”
Section: Discussionmentioning
confidence: 95%
“…Adopted from lit. 367,693,694 direct insertion of the glycomimetic lipid conjugate, similar effects on B cells could be induced. Inhibition of cellular activation, reduction of cytokine secretion and cellular proliferation were achieved.…”
Section: Cd22 Targeting -Siglec-engaging Tolerance-inducing Antigenic...mentioning
confidence: 97%
“…The elucidation of the precise role of nuclear PAF receptors 92,142,143 and orphan receptors, 144 and receptor dimers 145 that may recognize PAF and Lyso‐PAF as their cognate ligands is also needed. We eagerly await more progress in the PAF receptor mechanisms of action and the creation of next generation of PAF receptor antagonists, 8 perhaps those that can be conjugated to other disease‐modifying drugs, siRNAs and/or antibodies 146–149 . In fact, PAF‐neutralizing antibodies may prove effective in some of the diseases caused by PAF akin to what has been achieved by anti‐VEGF biologics, 150–152 and more recently by use of bispecific antibodies 153 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…We eagerly await more progress in the PAF receptor mechanisms of action and the creation of next generation of PAF receptor antagonists, 8 perhaps those that can be conjugated to other disease‐modifying drugs, siRNAs and/or antibodies. 146 , 147 , 148 , 149 In fact, PAF‐neutralizing antibodies may prove effective in some of the diseases caused by PAF akin to what has been achieved by anti‐VEGF biologics, 150 , 151 , 152 and more recently by use of bispecific antibodies. 153 Exciting new technologies and other forms of therapeutic agents as mentioned above need to be applied to PAF and its receptors to help advance this field of study.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%